THE EFFECTIVENESS OF IMPLEMENTING INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN HIGHER EDUCATION (Uzbekistan Open Conference, 2025)
This article explores the importance of implementing innovative pedagogical technologies in higher education and their impact on students’ learning activity, motivation, and academic performance. The study was conducted at the Jizzakh Branch of Kazan Federal University and examined the effectiveness of innovative approaches through a comparative analysis of experimental and control groups. The application of project-based learning, the flipped classroom model, problem-based learning, interactive lessons, and digital learning platforms enhanced students’ independent thinking, teamwork, and creativity. The results indicate that innovative technologies play a crucial role in improving the quality of education and should be implemented gradually and systematically across the higher education system.